GRP-174 Significance of Potentially Inappropriate Medicines For Elderly Patients at a German University Hospital. (12th March 2013) - Wickop, B; Härterich, S; Baehr, M; Langebrake, C
Abstract : Background: Certain drugs are classified as potentially inappropriate medication (PIM) for the elderly because they bear an increased risk of adverse drug events resulting in major safety concerns. Several classifications have been published to identify and avoid PIM. For this study FORTA [1] (fit for the aged), PRISCUS [2] (Latin: time-honoured) and STOPP [3] (Screening Tool of Older Persons' potentially inappropriate Prescriptions) criteria have been chosen as the most relevant ones. Purpose: The aims are to determine which PIM are taken by elderly patients at University Medical Center Hamburg-Eppendorf (UKE) and how the prevalence of PIM changes from admission to discharge. Materials and Methods: Based on the criteria provided by FORTA, PRISCUS and STOPP, medication of patients >65 years is screened within three point prevalence analyses at admission, during inpatient stay and at discharge, respectively. Medication is recorded and correlated to diagnoses and reason for admission. Patients are included in the study if they were admitted via the emergency department with at least five drugs prescribed on admission. Results: 660 patients were screened until 10/2012. 107 patients met the inclusion criteria, 63% of them were female, 64% (68/107) received at least one PIM at admission (48, 29 and 50 patients as defined by FORTA, PRISCUS and STOPP, respectively; multiple classifications possible), 82% (88/107) received PIM during inpatient stay (59 FORTA, 62 PRISCUS, 55 STOPP) and 57% (61/107) at discharge (40 FORTA, 27 PRISCUS, 48 STOPP). Zopiclone was the most often (29%) prescribed PIM during inpatient stay. Conclusions: Data of the interim analysis show that a high proportion of inpatients received PIM. Once the data acquisition is completed, further evaluation is needed to determine the consequences of PIM use, the correlation to reason for admission, which classification is best to detect PIM in hospitals and how the use of PIM at UKE can be minimised. References: M. Wehling, H. Burkhardt: Arzneitherapie für Ältere, Springer, 2. Auflage, 2011  Dtsch Arztebl Int, 2010;107(31–32):543–51  Int J Clin Pharmacol Ther, 2008 Feb;46(2):72–83 No conflict of interest.